Case Report: A Pathogenic Missense Variant of WT1 Cosegregates With Proteinuria in a Six-Generation Chinese Family With IgA Nephropathy - Li, Qianqian; Zhu, Li; Shi, Sufang; Xu, Damin; Lv, Jicheng; Zhang, Hong (Frontiers in Medicine, 2022)
IgA nephropathy (IgAN) is the most common type of primary glomerulonephritis worldwide. In addition to hematuria, proteinuria is observed in a considerable proportion of patients with IgAN and has proven to be a strong risk factor for disease progression. Although the exact pathogenesis of IgAN is still unclear, genetic factors are widely considered to play a role in its occurrence and development. Here, we investigated a large IgAN-associated pedigree of 47 members belonging to six generations. Two members of the family who presented with proteinuria and hematuria were diagnosed with IgAN through renal biopsy. Four other members also exhibited proteinuria or hematuria but without renal biopsy. Using whole-exome sequencing, we identified a likely pathogenic variant in WT1 (c.1397C>T; p.Ser466Phe) that co-segregated with proteinuria in the affected family members. In addition, another pathogenic variant in NPHS1 (c.3478C>T; p.Arg1160Ter) was identified; however, it did not co-segregate with abnormal proteinuria. Compared to individuals in the pedigree with only one heterozygous WT1 variant (c.1397C>T; p.Ser466Phe), the proband and her younger brother carried an additional WT1 variant (c.1433-10G>A) and presented with a more severe phenotype and rapid progression to end-stage kidney disease. Our findings suggest the WT1 missense variant (c.1397C>T; p.Ser466Phe)-induced primary podocyte injury might contribute to the proteinuria phenotype and IgAN progression in this pedigree.